Disruptive Technologies in Logistics outsourcing - Jadhav, Vaibhav A. (Cranfield University, 2025)
This study examines the transformation of third-party logistics (3PL) outsourcing relationships by disruptive technologies through a systematic research review of 50 peer-reviewed journal articles produced in the years 2020-2025. The study discusses the adoption and implementation of Artificial Intelligence (AI), Blockchain, and Internet of Things (IoT) technologies by 3PL service providers and how they impact operational effectiveness, competitiveness, and value co-creation in logistics outsourcing relationships. The research methodology adopts a systematic literature review guided by the Research Onion model and the PRISMA protocols and implements thematic analysis in synthesising the findings in the five interrelated themes of conceptualising disruption in logistics outsourcing, blockchain and trust mechanisms, AI and predictive optimisation, IoT and digital infrastructure, and value creation and strategic transformation. Key insights suggest that logistics disruption by technology outsourcing is relational and systemic and not merely tech adoption. IoT provides the foundation data infrastructure, blockchain enables algorithmic trust mechanisms, and AI provides the most grounded performance gains through predictive analytics. The technologies create paradoxes which necessitate sophisticated organisational capabilities to manage competing needs between efficiency and robustness, clarity and secrecy, innovation and stability. The study’s most notable theory contribution is the Technology-Enabled Value Co-Creation Framework that demonstrates value creation occurs through the integration of technology infrastructure, organisational capabilities, and contextual moderators rather than single-technology implementation. The framework identifies digital stratification as a major concern, such that the technology-enabled 3PLs derive disproportionate value while the small providers experience increasing competitive disadvantage. Practical wisdom suggests that the effectiveness of technology implementation relies on the development of dynamic capabilities for paradox management, technology integration ecosystem thinking, and context-level adaptation strategies. The research finds the requirement for industry standards across the industry, the deployment of ethical AI governance frameworks, and policies deconcentrating excessive digital leaders' market concentration
Keywords: disruptive technologies; third-party logistics; 3PL; logistics outsourcing; artificial intelligence; blockchain; Internet of Things; value co-creation; digital transformation; systematic literature review